Female Athlete Triad (FAT) Screening Using LEAF Questionnaire: A Cross-Sectional Study in Indonesia Pencak Silat Athletes - Itsna Rosyada; Sapta Kunta Purnama; Budiyanti Wiboworini (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
Health information acquired from a health examination or screening is one of the requirements for participating in the Pencak Silat tournament. Unfortunately, the most common health tests cover only vital signs and weight checks. Those tests cannot accurately describe a person's health status, such as digestive and menstrual disorders, common among female athletes due to intensive physical training and the pressure to maintain body weight according to the tournament category. The Female Athlete Triad (FAT) is the name given to this condition. This is the first study to use the LEAF questionnaire to assess the risk of FAT in female Indonesian Pencak Silat athletes. This is an observational study using a cross-sectional design. Data were collected online from 207 participants using a purposive random sampling approach. According to the findings of this study, 53.6% (N = 111) of 207 respondents were at risk of FAT. The risk variables were closely associated with the number of exercise hours per week (P = 0.012) and education level (P = 0.023). The high prevalence of FAT and its high risk indicate the necessity for FAT screening as a requirement for competing in the Pencak Silat tournament and prevention of early osteoporosis and uterine function abnormalities in female Indonesian Pencak Silat athletes. Furthermore, FAT screening on female athletes in all sports is required to prevent the long-term clinical implications of FAT.